Shadows of Berlin : a novel - Gillham, David R. (Naperville, Illinois : Sourcebooks Landmark, 2022)
"1955 in New York City, the city of progress. But in the Perlman residence, the past is as close as the present. Rachel Perlman, a child of Berlin and an artist bearing her mother's legacy, arrives in New York as part of the wave of Jewish Displaced persons who managed to survive the brutalities of the war. But despite her efforts, Rachel is unable to live the "normal" life of an American housewife, not until she can shake the ghosts of her past and the tremendous guilt that weighs down on her, her own "crime" of survival"--.
new book 2022 spring.
Keywords: Novels